Pelatihan Meningkatkan Wawasan Dan Keterampilan Strategi Meningkatkan Minat Membaca di Sekolah SMPN 2 Sukodono Kabupaten Sidoarjo - Indayani; Taufik Nurhadi; Tri Indrayanti (Universitas PGRI Adi Buana Surabaya, 2022)
The training aims to increase insight and strategies to increase interest in reading at SMPN 2 Sukodono, Sidoarjo Regency. Based on the results of preliminary observations and discussions with the Principal and Deputy Head of SMPN 2 Sukodono Sidoarjo, they are still having trouble finding the right strategy for literacy in students' reading interest by combining library management as a learning resource with digital information technology, especially in the preparation of literacy strategies for students' reading interest involving libraries. managed by the village/kelurahan government which is still conventional. Implementation of the program with the theme Optimizing School Literacy Cultivation at SMPN 2 Sukodono Sidoarjo with the sub-theme Training Improving Strategic Insights and Skills Improving Reading Interest in Schools in August 2021 s.d. September 2021 with the zoom meeting app. The results of this activity were carried out well. Training to increase insight and strategies to increase reading interest in schools includes literacy of students' reading interest, perspectives of school and village libraries in the digital era, the presence of digital technology in relation to students' reading interest, and strategies to increase student interest in reading. Education and literacy of students' interest in reading is carried out to prevent the decline in student achievement, especially the decline in reading interest.